The impact of the COVID-19 pandemic on thyroid nodular disease: a retrospective study in a single center in the western part of Romania - Popa, Oana; Barna, Robert Alexandru; Borlea, Andreea; Cornianu, Marioara; Dema, Alis; Stoian, Dana (Frontiers in Endocrinology, 2023)
The COVID-19 pandemic had a significant impact on the healthcare system, leading to a prioritization of hospital admissions in many countries. Romania was no exception, and it had to restrict patient access to medical services in hospitals with chronic diseases and oncological pathology, including thyroid cancer. This study aimed to compare the clinical and pathological factors of patients with nodular thyroid disease diagnosed and surgically treated during the two years before and after the COVID-19 pandemic, in a single medical institution. The retrospective study included 1505 patients who were diagnosed and operated on for nodular thyroid disease between January 2018 and December 2021. The patients were divided into two groups: the "PRECOVID" group (January 2018 to February 2020), and the "POSTCOVID" group (March 2020 to December 2021). The analyzed parameters included patient gender, age, preoperative diagnosis, type of surgical intervention, and pathological diagnosis. The results showed a significant decrease in the number of surgeries performed for thyroid nodular disease during the COVID-19 pandemic period (450 versus 1055 cases, p<0.00001). There was a significant decrease in the number of surgical reinterventions (0.9% in the POSTCOVID group versus 2.9% in the PRECOVID group, p=0.01), and a significant increase in the number of total thyroidectomies (84.9% in the POSTCOVID group versus 80.1% in the PRECOVID group, p=0.02). We also observed a higher incidence of malignant/borderline tumors in the POSTCOVID group compared to the PRECOVID group (p=0.04) and a significantly higher frequency of aggressive forms of thyroid cancer in the POSTCOVID group (p=0.0006). The COVID-19 pandemic had a significant impact on the surgical management of nodular thyroid disease, resulting in a decrease in surgeries and a change in the type of surgical interventions performed. The higher incidence of malignant/borderline tumors diagnosed during the pandemic highlights the importance of timely diagnosis and treatment of thyroid nodules to prevent cancer progression.